Contribuição metodológica para previsão da capacidade de carga de estacas raiz em rochas brandas - Santos Neto, João Firmino dos (2022)
This work presents a study related to the prediction of the load capacity of deep foundations embedded in rocks taking as reference results of load tests (PCE's) with the objective of developing an empirical formulation to predict the load capacity of root piles embedded in rocks. bland, adapting the proposal by Mascarenhas (2018). To carry out the research, data from mixed surveys and PCE's of works located on the border between Pernambuco and Piauí, as well as in Campo Largo in Bahia, were used. The geotechnical characterization of the rock sublayers was carried out from the results of the mixed drilling and considering some recommendations contained in the DNER-PRO 102/97 Standard (DNER, 1997). It was observed that the Qult predictions made from the semi-empirical methods applied in the development of the present research did not show agreement with the reference values ​​obtained from PCE's. This disagreement is attributed to the fact that the methods used require values ​​of uniaxial strength of the rock and deformability that, in the analyzes performed, were obtained by correlation. The method developed and proposed in this research, on the other hand, used pile geometry data and the GSI Geomechanical Classification. The validation of the proposed formulation indicated the agreement between the predicted values ​​of Qult and the experimental reference values. It is also worth noting that the proposed methodology has the advantage of being easy to apply, since it only uses information from the GSI classification.